A New Anhydrous Polar Rare-Earth Iodate Fluoride, Ce(IO3)2F2, Exhibiting a Large Second-Harmonic-Generation Effect and Improved Overall Performance - Zhang, Xiao-Han; Yang, Bing-Ping; Hu, Chun-Li; Chen, Jin; Huang, Qian-Ming; Mao, Jiang-Gao (Chemistry of materials, 2021)
A new anhydrous rare-earth metal iodate fluoride, Ce(IO3)2F2, was rationally designed and synthesized. Ce(IO3)2F2 features unique zigzag ∞[CeF2]2+ chains that are bridged by IO3 – groups, creating a complex three-dimensional structure, which is conducive to the orderly arrangement of the lone pair of the functional IO3 – groups and reinforcing the polarity compared to the hydrous material Ce(IO3)2F2(H2O). Ce(IO3)2F2 possesses a large second-harmonic-generation effect that is ∼5.5 times larger than that of the benchmark KH2PO4, a wide transmission range of 0.45–11.4 μm, and a high laser damage threshold (116.8 MW cm–2). Anhydrous Ce(IO3)2F2 is superior to the hydrous material and is a potential nonlinear optical material.